Pobreza, conflicto armado y convergencia (2017)
"The armed conflict phenomenon has left a mark on colombian history for more than 6 decades, leaving millions of victims throughout the years, destroying physical and human stock, and therefore generating higher poverty levels. The goal of this research article is to identify the effect of armed conflict on the behaviour of departamental monetary poverty levels, as well as the effect on the colombian departments' divergence or convergence tendencies. With this aim, simple regressions are made, controlled by fixed effects. The analysis unit is a 24 department pool. The convergence is analysed based on Barro and Sala-i-Martin's proposal. The investigation's result shows the existence of a positive and statistically significant effect of the armed conflict on the growth rate of poverty and on the conditional speed of convergence of departamental poverty levels." -- Tomado del Formato de Documento de Grado.